Mediation in peacekeeping missions - Wall, James A. Jr; Druckman,Daniel (Sage Publication Inc., 2003)
Mediation in peacekeeping missions and the role of dispute severity, time pressure, and the peacekeeper's rank in that process are investigated. A set of hypotheses concerning the effects of these factors is developed. A test of the hypotheses reveals that dispute severity has a strong effect on the peacekeepers' choice of techniques. Time pressure does not influence technique selection or interact with dispute severity, and rank has a moderate effect on technique choice. Contributions to the peacekeeping literature are discussed, and implications are developed for an agenda of research on mediation processes.